Accounting judgement as basis of innovative development of accounting and analytical management - T.O. Tarasova (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The most significant and researched accounting innovation is a professional judgement of a specialist in the context of accounting theory and methodology and is one of first tasks that requires solving. The author proposes the model of professional judgement as the product of intellectual activity; in accordance to the author’s model professional judgement is considered as the process of intellectual potential transformation (specialist’s formed competences) on innovative decision. Such accounting innovation is introduced to the management system according to logica structure: the generation of management decision – the analysis of management decision – the commercial use of management decision. To work out the criteria, which characterize the quality of professional judgement of an accountant and the level of their priority when choosing professionals, the author suggests the methodology of assessment of professional judgement of a specialist in the field of accounting, and this methodology provides the determination of quantitative and qualitative criteria of their professional usefulness on the base of determination of their priority grade. The proposed methodological approach concerning the assessment of professional judgement can be used in the system of personnel management for recruiting agencies that according to employers’ order make selection of highly qualified personnel to perform managerial accounting and analytical functions in structural subdivisions of big trade nets. The system of assessment in the Federation of Certified professional accountants requires correcting, that is why, it is useful to add the suggested methodology to the existing system of traditional assessment-testing that will allow to form the rating of experienced accountants, and increase their professional motivation.